2006
DOI: 10.1016/j.virol.2006.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ and interleukin-4 downregulate expression of the SARS coronavirus receptor ACE2 in Vero E6 cells

Abstract: Interferons (IFNs) inhibit severe acute respiratory syndrome coronavirus (SARS-CoV) replication and might be valuable for SARS treatment. In this study, we demonstrate that treatment of Vero E6 cells with interleukin-4 (IL-4) decreased the susceptibility of these cells to SARS-CoV infection. In contrast to IFNs, IL-4 did not show antiviral activity when administered immediately after SARS-CoV infection, suggesting that IL-4 acts early during the SARS-CoV replication cycle. Indeed, binding of recombinant SARS-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(112 citation statements)
references
References 41 publications
5
105
1
1
Order By: Relevance
“…De Lang and colleagues reported that IL-4 and IL-13 decreased ACE2 expression in Vero E6 cells (32). However, as shown in Figure 1, we found that IL-4/IL-13 actually increased ACE2 expression in our primary human alveolar type II cells.…”
Section: Discussioncontrasting
confidence: 54%
“…De Lang and colleagues reported that IL-4 and IL-13 decreased ACE2 expression in Vero E6 cells (32). However, as shown in Figure 1, we found that IL-4/IL-13 actually increased ACE2 expression in our primary human alveolar type II cells.…”
Section: Discussioncontrasting
confidence: 54%
“…Pretreatment of cells with interferon before infection prevents SARS-CoV replication in these cells [53]. Interestingly, it has been demonstrated that IFN-γ downregulates expression of ACE2, the cellular SARS-CoV receptor, on the cell surface, resulting in decreased infection in these cells [54]. In addition, Haagmans and coworkers showed that IFN-α protects type-I pneumocytes from SARS-CoV infection in macaques [55].…”
Section: Future Perspectivementioning
confidence: 99%
“…Although the Vero E6 cell line lacks the ability to transcribe type I IFNs as these cells possess a genetic deletion, research has indicated that the cells mount a weak initial IRF3-dependent response to various ligands, inducing a weak innate response to viruses [19]. With respect to coronaviruses, upon IFNs binding to the corresponding receptors, a downstream signaling is initiated and acts to block one or more steps in the virus life cycle [20]. Mammalian target of rapamycin (mTOR) plays a vital role in monitoring the availability of nutrients, mitogenic signals and cellular energy, and is a necessary part of the phosphatidylinositol 3-kinase (PI3K) cell survival pathway [21].…”
Section: Introductionmentioning
confidence: 99%